ANATOMI DAUN TANAMAN HIAS DIKOTIL YANG DIPENGARUHI TRANSPIRASI DALAM MEDIA ATLAS - Rahman, Galih Fathur; Daningsih, Entin; Mardiyyaningsih, Asriah Nurdini (Universitas Tanjungpura, 2023)
The structure and function of plant tissue was difficult material for students to learn, especially in identifying plant tissue due to limited laboratory facilities such as plant tissue preparations. Learning media could help students in overcoming these problems that could display plant tissue clearly. The atlas media contained anatomical pictures of the leaves of six types of dicot ornamental plants which could help students to observe plant tissues. This study aimed to determine the validity of the leaf anatomy atlas media of six types of dicot ornamental plants in the structure and function of the sub-material of plant tissue in class XI. The research method was quantitative descriptive. Progress in making atlas consists of pre-production, production, and post-production. The media atlas was validated by five validators with a Likert scale (1-4). The validated aspects were presentation, content, language, and usage with 21 criteria. The data were analyzed using Laswhe method. The results of the validation showed that the aspects of language and usage obtained reached the minimum value of the Lawshe index of 0.99 but the presentation and content aspects have not reached the minimum value of the Lawshe index. The results of the validation show that the atlas media was not yet valid, especially in terms of presentation and content, so the atlas needs to be revised before being used in the classroom.